KIF13A mediates influenza a virus ribonucleoproteins trafficking - Ramos-Nascimento, Ana (2017)
Influenza A is a rapid evolving virus, successful in provoking periodic epidemics and occasional pandemics in humans. Viral assembly is complex as the virus incorporates an eight-partite segmented genome of RNA (in the form of viral ribonucleoproteins, vRNPs). Genome assembly, with implications to public health, is not completely understood. It was reported that vRNPs are transported to the cell surface on Rab11 vesicles using microtubules, but no molecular motor has been assigned to the process. Here, we have identified KIF13A, a member of the kinesin-3 family, as the first molecular motor efficiently transporting vRNP-Rab11 vesicles during IAV infection. Depletion of KIF13A resulted in reduced viral titres and less accumulation of vRNPs at the cell surface, without interfering with the levels of other viral proteins at sites of viral assembly. In addition, in overexpression conditions and using two artificial methods able to displace vRNP-Rab11 vesicles, KIF13A augmented vRNP levels at the plasma membrane. Together our results show that KIF13A is an important host factor promoting influenza A vRNP transport, which is a crucial step for viral assembly.